Locations of Motor Vehicle Theft and Recovery - Suresh, Geetha (American journal of criminal justice, 2013)
In a community-level analysis, this study examines risky locations for motor vehicle theft in Louisville, Kentucky from 2004 to 2007. Maps will display clustering patterns, density, displacement of motor vehicle thefts and relationships with spatial attributes and neighborhood characteristics. Clustering indicates heavy concentration of motor vehicle theft and recovery in the neighborhoods characterized by indicators of social disorganization (poverty, unemployment, vacant houses). Parking lots belonging to churches in a socially disorganized neighborhood are also an auto crime attractor.